2000
DOI: 10.1086/317461
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Achromobacter xylosoxidans Bacteremia Associated with Persistent Lymph Node Infection in a Patient with Hyper-Immunoglobulin M Syndrome

Abstract: Achromobacter xylosoxidans (formerly Alcaligenes xylosoxidans) is a rare but important cause of bacteremia in immunocompromised patients, and strains are usually multiply resistant to antimicrobial therapy. We report an immunocompromised patient with hyper-immunoglobulin M syndrome who suffered from 14 documented episodes of A. xylosoxidans bacteremia. Each episode was treated and resulted in rapid clinical improvement, with blood cultures testing negative for bacteria. Between episodes, A. xylosoxidans was is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 32 publications
(42 reference statements)
0
40
0
2
Order By: Relevance
“…The U.S. Cystic Fibrosis Foundation's National Patient Registry reported an increase of 4.5%, from 1995 to 2002 (1, 2), in the frequency of isolation of this microorganism from CF patients. Recently, A. xylosoxidans has been considered a nosocomial pathogen, particularly in immunocompromised patients, causing a variety of infections, including bacteremia, meningitis, pneumonia, and peritonitis (8,23,25). Achromobacter spp.…”
mentioning
confidence: 99%
“…The U.S. Cystic Fibrosis Foundation's National Patient Registry reported an increase of 4.5%, from 1995 to 2002 (1, 2), in the frequency of isolation of this microorganism from CF patients. Recently, A. xylosoxidans has been considered a nosocomial pathogen, particularly in immunocompromised patients, causing a variety of infections, including bacteremia, meningitis, pneumonia, and peritonitis (8,23,25). Achromobacter spp.…”
mentioning
confidence: 99%
“…A. xylosoxidans is an opportunistic pathogen that causes healthcare-associated infections, including bacteremia, meningitis, pneumonia, endocarditis, peritonitis, osteomyelitis, urinary tract infection, and endophthalmitis, in vulnerable hosts, including neonates, burn victims, and other immunocompromised patients. [191][192][193] Among 341 individuals with CF in the United States infected with Achromobacter, 42% were infected with A. xylosoxidans, and 23.5% were infected with Achromobacter rhulandii. 190 In 2 small single-center studies, Achromobacterinfected individuals each harbored genotypically distinct strains.…”
Section: Iiia3 Other Gram-negative Bacteriamentioning
confidence: 99%
“…Mortality rates of up to 80% have been reported in infections of A. xylosoxidans in neonates (9). The case mortality rate is reported to be as high as 30% in adult cases of bacteremia and up to 65% in cases of meningitis, endocarditis, and pneumonia (9,44). Gomez-Cerezo et al identified risk factors associated with increased mortality to include older age (over 65 years) and neutropenia (17).…”
Section: Case Reportmentioning
confidence: 99%